Gangbusters, mavericks, and the cop next door: dominant models of American policing in popular culture = Wunderkinder, Einzelgänger und der Polizist von Nebenan - Bielejewski, Aaron (Kriminologisches Journal, 2016)
Depictions of policing in popular culture have shifted throughout the history of film and television. Focusing on the role of individual officers within the organization, this article explores four eras in the cultural presentation of policing. The professionalism era of policing offered an image of police officers as idealized representations of their organization, but this model was eventually replaced with an individual-centric view of policing. More modern examples suggest a new model which separates the individual from the policing role and presents a more complex character. Elements of the professional model of policing, particularly the crime fighter image, however, were transported into this new model and remain essentially unchallenged.